Strategi Pembelajaran IPAS dengan Model PANUTAN; Meningkatkan Partisipasi, Keterampilan Kritis dan Kerja Sama Siswa - Mahmudah .; Ahmad Suriansyah; Ratna Purwanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
In the era of Society 5.0, students are required to master critical thinking and collaboration skills in order to be able to face the challenges in this era. However, in reality, fourth grade students of SDN Telaga Sili-Sili have not mastered these two skills, this is proven by the test results which show that students are not optimal in understanding the material and are not yet competent in completing the challenges given by the teacher, students have not been able to apply collaboration skills well because some students prefer to learn individually and only 4 out of 10 students reach the KKTP limit. This study aims to use the PANUTAN model to test student learning outcomes, critical thinking skills, collaboration skills, and activities. PTK is the method used in this study which was carried out in 4 meetings. Based on the results of the study, student activity increased from 40% at meeting 1 to 80% at meeting 4. At meeting 1 the percentage of critical thinking skills was 30%, at meeting 4 it increased to 90%. At meeting 1 collaboration skills were 40%, and at meeting 4 it increased to 90%. From meeting 1 to meeting 4, it increases student learning outcomes from 30% to 100%. The results of the study indicate that the application of the PAMUTAN model is effective in improving learning outcomes, critical skills, cooperation and student activity.